2019
DOI: 10.1021/acs.nanolett.8b04083
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Positioning, Stability, and Segregation of Dopants in Hexagonal Si Nanowires

Abstract: We studied the physics of common p- and n-type dopants in hexagonal-diamond Si, a Si polymorph that can be synthesized in nanowire geometry without the need of extreme pressure conditions, by means of first-principles electronic structure calculations and compared our results with those for the well-known case of cubic-diamond nanowires. We showed that (i) as observed in recent experiments, at larger diameters (beyond the quantum confinement regime) p-type dopants prefer the hexagonal-diamond phase with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 77 publications
2
21
0
Order By: Relevance
“…By applying DFT based methods, we investigate the formation energy and the local crystal symmetry distortion for group III (B, Al, Ga), group IV (Si, Ge, C) and group V (N, P, As) dopants in Ge and C crystals, both for the 2H and 3C phase. We compare the obtained trends with results previously obtained for Si [37]. Our main findings can be summarized as follows: i) in diamond-type crystals the bulk sites symmetry (T d ) is preserved by doping while in hexagonal crystals the impurity site moves towards a higher (T d ) or lower (C 3v ) symmetry configuration dependently on the valence of the dopant atoms; ii) for Si and Ge, group III impurities can be more easily introduced in the hexagonal-diamond phase -whose local C 3v symmetry better accommodate the three-fold coordination of the impurity -while ntype impurities do not reveal any marked phase preference; iii) for C, both n and p dopants are more stable in the hexagonal-diamond structure than in the the cubic one, but this tendency is much more pronounced for n-type impurities.…”
Section: Introductionmentioning
confidence: 63%
“…By applying DFT based methods, we investigate the formation energy and the local crystal symmetry distortion for group III (B, Al, Ga), group IV (Si, Ge, C) and group V (N, P, As) dopants in Ge and C crystals, both for the 2H and 3C phase. We compare the obtained trends with results previously obtained for Si [37]. Our main findings can be summarized as follows: i) in diamond-type crystals the bulk sites symmetry (T d ) is preserved by doping while in hexagonal crystals the impurity site moves towards a higher (T d ) or lower (C 3v ) symmetry configuration dependently on the valence of the dopant atoms; ii) for Si and Ge, group III impurities can be more easily introduced in the hexagonal-diamond phase -whose local C 3v symmetry better accommodate the three-fold coordination of the impurity -while ntype impurities do not reveal any marked phase preference; iii) for C, both n and p dopants are more stable in the hexagonal-diamond structure than in the the cubic one, but this tendency is much more pronounced for n-type impurities.…”
Section: Introductionmentioning
confidence: 63%
“…Much less attention has been dedicated to the behaviour of dopants in 2H-Si-NWs. In a recent study 153 we performed ab initio DFT calculations to describe the properties of p-type and n-type dopants located at the innermost sites in 2H-Si-NWs, comparing our results with those obtained for 3C-Si-NWs. All the surface dangling bonds were saturated by H atoms.…”
Section: Doped Hexagonal Si-nwsmentioning
confidence: 98%
“…[140][141][142][143][144][145][146] In particular, Si-NWs showing the hexagonal-diamond (2H) phase have been the object of intense study because of their potential for adding new functionalities to 3C Si-NWs. The electronic, optical and transport properties of 2H-Si-NWs [147][148][149][150][151][152][153] have been under scrutiny, highlighting how this phase can offer a further degree of property modulation with respect to the versatility of 3C-Si-NWs. For example, it has been shown that 2H-Si-NWs are characterized by a more pronounced QC effect than 3C-Si-NWs and by a more enhanced optical absorption in the visible region.…”
Section: Hexagonal Si Nanowiresmentioning
confidence: 99%
See 2 more Smart Citations